Proteomic Basis of Symbiosis: A Heterologous Partner Fails to Duplicate Homologous Colonization in a Novel Cnidarian– Symbiodiniaceae Mutualism - Medrano, Emmanuel; Merselis, Daniel G.; Bellantuono, Anthony J.; Rodriguez-Lanetty, Mauricio (Frontiers in Microbiology, 2019)
Reef corals and sea anemones form symbioses with unicellular symbiotic dinoflagellates. The molecular circumventions that underlie the successful intracellular colonization of hosts by symbionts are still largely unknown. We conducted proteomic analyses to determine molecular differences of Exaiptasia pallida anemones colonized by physiologically different symbiont species, in comparison with symbiont-free (aposymbiotic) anemones. We compared one homologous species, Symbiodinium linucheae, that is natively associated with the clonal Exaiptasia strain (CC7) to another heterologous species, Durusdinium trenchii, a thermally tolerant species that colonizes numerous coral species. This approach allowed the discovery of a core set of host genes that are differentially regulated as a function of symbiosis regardless of symbiont species. The findings revealed that symbiont colonization at higher densities requires circumvention of the host cellular immunological response, enhancement of ammonium regulation, and suppression of phagocytosis after a host cell in colonized. Furthermore, the heterologous symbionts failed to duplicate the same level of homologous colonization within the host, evidenced by substantially lower symbiont densities. This reduced colonization of D. trenchii correlated with its inability to circumvent key host systems including autophagy-suppressing modulators, cytoskeletal alteration, and isomerase activity. The larger capability of host molecular circumvention by homologous symbionts could be the result of a longer evolutionary history of host/symbiont interactions, which translates into a more finely tuned symbiosis. These findings are of great importance within the context of the response of reef corals to climate change since it has been suggested that coral may acclimatize to ocean warming by changing their dominant symbiont species.